Statistical analysis of pyramid horn antenna response to high-altitude electromagnetic pulse - Dewei XIA; Chuanbao DU; Shengquan ZHENG; Congguang MAO; Fei CAO; Hui ZHANG; Zhitong CUI (Zhongguo Jianchuan Yanjiu, 2023)
ObjectiveThis paper aims to study the coupling response law of an electromagnetic pulse acting on a pyramid horn antenna under the condition of the random distribution of incident parameters. Methods First, a statistical analysis model of the electromagnetic pulse response of the horn antenna is established on the basis of a computer simulation technology (CST) and Matlab co-simulation. A simulation model of the antenna electromagnetic impulse response is then established by CST, and the rationality of the model is verified by the voltage standing wave ratio (VSWR) and gain curve. The impedance characteristics of the radio frequency port of the communication system under different states such as transmitting and receiving are considered. The coupling response indexes of antenna ports such as open circuit voltage (OCV), short circuit current (SCC) and load current are obtained under high-altitude electromagnetic pulse (HEMP) irradiation with a peak field strength of 50 kV/m. Finally, the azimuth, elevation and polarization angles are set in the spherical coordinate system to obey the uniform distribution, and Matlab is used to fit the main signal indicators such as the peak value and waveform energy of the antenna load response waveform. ResultsThe results show that the probability distribution of the main signal indicators is mostly convex. Taking the waveform peak value as an example, there is a 90% probability that the peak value of the response waveform is less than 0.13A, which is only 16.2% of the maximum peak value of 0.8A; that is, except in the specific electromagnetic pulse incident range, the signal indicators of the pyramid horn antenna response waveform are kept at a low level in most cases.ConclusionThe results of this study lay the foundation for the electromagnetic pulse vulnerability analysis of communication systems.